Identification of Human Papillomavirus Type 58 Lineages and the Distribution Worldwide - Chan, P.K.S.; Luk, A.C.S.; Park, J.S.; Smith-McCune, K.K.; Palefsky, J.M.; Konno, R.; Giovannelli, L.; Coutlee, F.; Hibbitts, S.; Chu, T.Y.; Settheetham-Ishida, W.; Picconi, M.A.; et al. (Oxford University Press (OUP), 2011)
Background. Human papillomavirus type 58 (HPV-58) accounts for a much higher proportion of cervical cancers in East Asia than other types. A classification system of HPV-58, which is essential for molecular epidemiological study, is lacking.